(untitled) (Journal of the College of Basic Education, 2022)
The Bani Marin tribe is one of the tribes that is a model for the Bedouin tribe, which was able, thanks to the efforts of its first leaders and over the course of nearly sixty years of conflict with the Almohads, to impose itself strongly as a new tribal and political reality in the Far Maghreb after the influence of the Almohads began to decline after losing the battle of punishment in Andalusia In the year 609 AH / 1211 AD, in this difficult atmosphere, the Marinids entered the agricultural and civilized Al-Aqsa citizen of Morocco after they found that its people had abandoned it because of the harsh taxes imposed on them by the state and their loss of men in the Andalusian wars and internal conflicts, as the Marinids were able to control most of the valleys and cities of Morocco A struggle broke out with the crumbling Almohads, and their victories continued